Ciência e literatura em Lima Barreto - Tavares, Eva Volite Coelho (2015)
This work analyses Brazilian writer Lima Barreto with focus on his scientific view, as shown in his work, and investigates the relationship between Literature and History of Science. It took Triste fim de Policarpo Quaresma (Sad end of Policarpo Quaresma) as a reference, as well as chronicles and other author's productions, regarding the recognition of a dialogue between reality and fiction. It also investigated the writer s passage through the Polytechnic School of Rio de Janeiro and his readings and reflections on certain aspects of the scientific knowledge in vogue, motivated by intellectual sharing with literate men of his time. The analyzed period, between the end of the XIXth and the early XXth century, in the city of Rio de Janeiro, shows a context marked by a belief in progress and appreciation of science that had a profound influence on the creation of the author s characters. However, being a dissonant voice of his time, Lima Barreto reveled a distrust on the modernization discourse at the time and positioned himself critically towards the Republican regime based on positivist ideas